DEVELOPMENT OF ASTRONOMY LITERACY SCALE: A STUDY OF VALIDITY AND RELIABILITY - Benli Özdemir, Esra (International Online Journal of Education and Teaching, 2022)
The aim of this research is to develop a valid and reliable "Astronomy Literacy Scale" in order to determine the astronomy literacy levels of individuals. Quantitative research method was used in the study. The study group of the research consisted of 5th, 6th, 7th and 8th grade students consists of a total of 519 students studying in 3 different secondary schools in Ankara in the spring term of the 2021-2022 academic year. The data obtained after the application were analyzed with SPSS and Lisrel statistical programs. As a result of the factor analyzes carried out, it was seen that the developed scale was a structure consisting of a total of 15 items with 3 factors. The “Astronomy Literacy Scale (AOS)” consists of four separate parts and 21 judgments in a five-point Likert type. In the scale, part one, self-perception towards astronomy; the second part, the affective dimension to astronomy; the third part includes the behavioral dimension for astronomy and the fourth part includes the cognitive dimension for astronomy. In this research, it has been revealed that the "astronomy literacy scale", which aims to determine the astronomy literacy levels of individuals, is a valid and reliable measurement tool.